Assessment of Her‐2/neu status using immunocytochemistry and fluorescence in situ hybridization on fine‐needle aspiration cytology smears: Experience from a tertiary care centre in India. Issue 8 (20th December 2013) - Durgapal, Prashant; Mathur, Sandeep R.; Kalamuddin, Md.; Datta Gupta, Siddhartha; Parshad, Rajinder; Julka, Pramod K.; Panda, S. K.; Aisner, Dara
<x xml:space="preserve">Abstract</x> Breast carcinoma shows amplification/overexpression of Her‐2/neu in ∼20–30% of cases. The determination of Her‐2/neu expression accurately is vital in clinical practice as it has significant predictive value and eligibility for anti Her‐2/neu therapy. Amplification and overexpression of Her‐2/neu gene is traditionally identified by fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) on tissue sections; only a few studies have evaluated feasibility of these techniques on cytological smears. One hundred cases of breast cancer with fine‐needle aspiration cytology (FNAC) samples and corresponding surgically resected specimen were selected. Immunocytochemistry (ICC) and FISH for Her‐2/neu was done on FNA smears, whereas IHC was performed on corresponding tissue sections. Diagnostic accuracy of ICC was 99% when compared with IHC. Comparison of FISH results with IHC showed 100% concordance. Unlike many centers in West, FNAC is still routinely performed in developing countries like India where vast majority of breast cancer cases present as palpable lumps. The high rates of accuracy of ICC and FISH for Her‐2/neu detection can make FNAC a relevant first line of investigation as a cost effective model with a rapid turn‐around time, providing complete information necessary for initial management of breast cancer patients. Diagn. Cytopathol. 2014;42:726–731. © 2013 Wiley Periodicals, Inc.